A person-oriented analysis of hope in Chinese adolescents. (October 2016) - Ling, Yu; Huebner, E. Scott; Fu, Peng; Zeng, Yifang; He, Yushu
Abstract: Using latent class analysis, we explored the within-person configurations of hope in a sample of Chinese adolescents. A total of 1688 adolescents (801 boys and 887 girls) from Mainland China completed measures of hope, life satisfaction, self-esteem, and depression. Obvious grouping features appeared, and a model of the three latent classes was supported. The three classes of 'high hope', 'average hope', and 'low hope' accounted for 32%, 47.5%, and 20.5% of the variance respectively. Compared to the average- and low-hope classes, the high-hope class reported significantly higher levels of life satisfaction, self-esteem and optimism and lower levels of depression, suggesting that higher levels of hope are adaptive in non-Western cultures as well as Western ones. Highlights: Psychological benefits of hope generalized to youth from a collectivistic culture. Three classes of high, average and low hope groups were identified. Chinese youth with highest hope reported highest life satisfaction, self-esteem, and optimism and lowest depression.